Nonlinear optical investigation of (E)-1-(4-flourobenzylidene)urea using theoretical calculations - J, Tracy; A, Dhandapani; Bharani, Bharanidharan (International Journal of Advanced Chemistry, 2017)
The FT-IR and FT-Raman spectra of (E)-1-(4-flourobenzylidene)urea (4FBU) was recorded and analyzed. The optimized geometrical parameters were calculated. The complete vibrationally assignments were performed based on PED analysis with the help of SQM method. NBO analysis was carried out to explore the various conjucative/hyperconjucative interactions within the molecule and their second-order stabilization energy. The HOMO and LUMO energy gap was studied. All theoretical calculations were performed based on B3LYP/6-31G (d,p) level of theory. The first order hyperpolarizability (Î²0) and related properties (Î², Î±0, Î”Î±) of 4FBU were calculated. Besides, FMOs, MEP, Mulliken atomic charges and various thermodynamic parameters such as entropy, heat capacity and enthalpy were also calculated.